Photographic and descriptive musculoskeletal atlas of gorilla : with notes on the attachments, variations, innervation, synonymy, and weight of the muscles - Diogo, Rui,; Tuttle, Russell H., (Science Publishers, 2011)
"This first photographic and descriptive musculoskeletal Atlas of Gorilla differs from previous works done with gorillas and other primates in various ways. First, it includes numerous detailed high-quality photographs of musculoskeletal structures from most anatomical regions of the body. Second, it includes textual information about the attachments, innervation and weight of the reported muscles. Third, it is based on the dissections of various fresh gorillas, as well as on an extensive review of the works published by other authors, thus providing an updated review of the anatomical variations within gorillas as well as an extensive list of the synonyms used in the literature to designate the structures reported here. Fourth, the data previously obtained in the authors' dissections of numerous other primates, as well as of numerous other vertebrates, proved to be crucial for examining and understanding the homologies between the muscular structures of gorillas, humans, and other taxa. This Atlas will be of interest to students, teachers and researchers working in fields such as primatology, comparative anatomy, functional morphology, zoology, or physical anthropology, as well as to those medical students, doctors and researchers who are interested in understanding the origin, evolution, homology and variations of the musculoskeletal structures of humans"--